DETERMINING THE FACTORS RELATED TO FIRST TIME POSTNATAL BREASTFEEDING - Armita Mayang Sari (Universitas Airlangga, 2020)
Infant Mortality Rate (IMR) is a problem in Indonesia that must be addressed in various aspects. New-borns need more attention in fulfilling their intake for growth and development. The best baby intake for early life after childbirth is exclusive breast milk. The importance of the time when breastfeeding is first given is closely related to the success of the Early Breastfeeding Initiation (EBI). Besides being able to handle the problem of infant intake, EBI is useful in strengthening the relationship between mother and child due to the interactions formed during breastfeeding. The goal to be achieved by researchers is to determine factors related to the time when breastfeeding was first given after birth. This type of research is analytic descriptive using the Spearman correlation test and chi-square statistical tests. The data used are secondary data from the Indonesian Demographic and Health Survey (IDHS) in 2017. The results of the descriptive analysis of the study are that the majority of mothers as respondents gave breastfeeding for the first time immediately at 62.8%. The results of the bivariate analysis of the study are the relationship between maternal parity (p = 0.001 and r = -0.072), infant birth weight (p = 0.03 and r = 0.049), area of residence (p = 0.013) and type of delivery (p = 0.013) p = 0.001) to the time of first breastfeeding.